FREKUENSI MOLTING DAN SINTASAN LOBSTER AIR TAWAR (Cherax quadricarinatus) DENGAN PERSENTASE PAKAN TUBIFEX DAN KOMERSIAL YANG BERBEDA - sarmin Sarmin; Marhaendro Santoso; Kasprijo Kasprijo (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
Abstract Feeding is one component in the cultivation which plays a very large role in growth determination and in terms of production costs, given that freshwater crayfish is omnivorous that can be fed with commercial and tubifex feed. This study examines the influence of a combination of commercial and tubifex feed on moulting frequency and survival rate of freshwater crayfish. The research was conducted for 60 days; tested animals weighed 3±0.69 g and measured 5±0.34 cm, in average. Experimental design using Complete Randomized Design (CRD) was applied to examine 5 treatments in quadruplicates. Treatment P1 represented 0% tubifex and 100% commercial feed, P2= 25% tubifex and 75% commercial feed, P3= 50% tubifex and 50% commercial feed, P4= 75% tubifex and 25% commercial feed, P5= 100% tubifex and 0% commercial feed. The study showed that the survival rate and moulting frequency were not different between treatments. Moulting frequency between successive treatment were P1= 4.25±1.5, P2= 1.5±3.75, P3= 2.75±1.3, P4= 4±1.4, P5= 3.5±1.3. Survival rate between respective treatment were P1= 40±16.33%, P2= 30±25.82%, P3= 35±25.17%, P4= 30±25.82%, and P5= 45±25.82%. Key words: Cherax quadricaritanus, feed, molting, survival, tubifex.